1728. Effectiveness and Healthcare Personnel (HCP) Perceptions of a Multi-Site Personal Protective Equipment (PPE) Free Zone Intervention. (26th November 2018) - Visnovsky, Lindsay; Mulvey, Diane; Zhang, Yue; Leecaster, Molly; Donskey, Curtis J; Krein, Sarah L; Safdar, Nasia; Alhmidi, Heba; Barko, Lauren; Haroldsen, Candace; Ide, Emma; Nevers, McKenna; et al.
Abstract: Background: CDC provides guidelines for using contact precautions (CP) when caring for patients with antibiotic-resistant bacteria or Clostridium difficile . However, HCP frequently report discomfort, difficulty of use, and interrupted workflow with CP. Modifying CP guidelines to balance these issues requires testing to assess benefits and maintenance of safe practices. A promising approach using a "PPE Free Zone" strategy within rooms of patients in CP has not been well-studied. Methods: The PPE Free Zone comprised a 3–6 foot area inside door thresholds of CP patient rooms denoted by red tape placed on the floor. Within the zone, HCP were not required to don PPE. HCP were considered compliant if they performed hand hygiene (HH) and donned appropriate PPE before crossing the zone. Observers at 6 acute care facilities (ACF) were trained on observing HCP HH and use of PPE with CP. Observations were made before and after implementation of a PPE Free Zone. Intervention ACF conducted observations on 8 intervention units and 6 nonintervention units. Models of overall compliance and entry HH compliance were constructed using a generalized linear-mixed effects model with a logistic link function. Pre-intervention observations from all 6 ACF and intervention phase observations from the 3 intervention ACF were used in models. Results: We observed 4, 510 room entries. HH adherence declined over time in both intervention and control units but declined less among intervention units from pre to post intervention (β: 0.71, P = 0.007, Figure 1). Stratified by precautions type, the effect of the PPE Free Zone on HH was only significant for rooms in enteric precautions ( P < 0.001). Compliance with PPE use was not significantly different pre- versus postintervention ( P = 0.133). When surveyed, HCP had positive views of the PPE Free Zone: 65% ( n = 172) agreed or strongly agreed the zone facilitates communication with patients, permits checking on patients more frequently, and saves time [ n = 169] (Figure 2). Conclusion: Although HCP viewed the zone positively and it had a significant effect on HH in enteric precautions rooms, the zone did not improve PPE compliance. Future interventions in the ACF setting should consider the complex sociotechnical system factors influencing behavior change. Disclosures: All authors: No reported disclosures.